Aminoglycosides can be a better choice over macrolides in COVID-19 regimen: Plausible mechanism for repurposing strategy (2020)
In the current COVID-19 pandemic, prioritizing the immunity enhancers is equally important to anti-virals. Defensins are the forgotten molecules that enhance the innate immunity against various microbes. Although macrolides like azithromycin and clarithromycin etc., have been reported to act against respiratory infections but they lack the ability of immunity enhancement through defensins. The aminoglycosides were proved to have defensin mediated antiviral activity, that could enhance the immunity. So, Consideration of aminoglycosides can be a double edge sword viz., against respiratory infection as well as Immunity enhancer (along with anti-virals) for COVID-19 regimen.